The role of IL-6 on apical periodontitis: a systematic review - Azuma, M. M. [UNESP]; Samuel, R. O. [UNESP]; Gomes Filho, João Eduardo [UNESP]; Dezan Junior, Eloi [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (Wiley-Blackwell, 2014)
The aim of this review was to examine current knowledge of the role of interleukin-6 (IL-6) in apical periodontitis (AP) pathogenesis as an inflammatory or pro-inflammatory cytokine. It also looked at whether IL-6 could serve as a measure for differential diagnosis or as a biomarker that can further predict the progression of bone resorption. A systematic review relating to AP and IL-6 was made via PubMed, BIOSIS, Cochrane, EMBASE and Web of Science databases using keywords and controlled vocabulary. Two independent reviewers first screened titles and abstracts and then the full texts. The reference lists of the identified publications were examined for additional titles. Eighteen papers were studied in total. In vitro studies (n = 6) revealed that IL-6 is present in AP, and its levels are proportional to the size of the periapical lesions. Neutrophils and macrophages resident in these lesions can produce IL-6 in vitro after a bacterial stimulus. Animal studies (n = 5) showed that IL-6 is present in AP and that osteoblasts can produce IL-6 in vivo. On the other hand, two studies using IL-6 knockout mice revealed larger periapical lesions when compared with control groups, demonstrating IL-6's role as an anti-inflammatory cytokine. In human studies (n = 7), IL-6 was identified in AP, and its levels were higher in symptomatic, epithelialized and large lesions than in asymptomatic and small lesions. These data lead to the conclusion that IL-6 may play a pro-inflammatory role, increasing its levels and reabsorbing bone in the presence of infections. When IL-6 is not present, other cytokines such as IL-1 and TNF-alpha induce bone resorption. Further studies about the relationship between AP development and the cytokine network must be performed to establish the exact role of each cytokine in the inflammatory process.
Keywords: apical periodontitis; interleukin-6; periapical lesions; systematic review